Патентоведение: учебник для вузов - Артемьев Е. И. Евгений Иванович; Богуславский М. М.; Вчерашний Р. П.; Рясенцев В. А. Владимир Александрович (Москва, Машиностроение, 1984)
Авт. указаны на обороте тит. л.